State and Guidelines for Participation in Academic Administration of Teachers Under Buriram Primary Educational Service Area Office 2: State and Guidelines for Participation in Academic Administration of Teachers Under Buriram Primary Educational Service Area Office 2 - พินิจนาม จิวาลักษณ์; Thauyngam, Kitiwat; Sri-ngan, Kraphan (RATANABUTH JOURNAL, 2026)
The purposes of this study were to examine 1) the current state of teachers’ participation in academic administration in schools, and 2) guidelines for enhancing teachers’ participation in academic administration in schools. A mixed-methods research design was employed. The sample consisted of 331 teachers, selected using the Krejcie and Morgan table with stratified random sampling, while 7 key informants were purposively selected for interviews. Research instruments included a questionnaire with a reliability coefficient of .95 and a semi-structured interview form. Data were analyzed using percentage, mean, standard deviation, and content analysis. The findings revealed that 1) the overall current state of teachers’ participation in academic administration was at a high level ( = 4.23, S.D.= 0.49). 2) A total of 74 guidelines were proposed regarding participation in decision-making and implementation. The guidelines aimed to shift teachers’ roles from passive recipients to active participants in all administrative processes. Priority guidelines included enabling teachers to collaboratively determine curricula in a bottom-up approach, implementing authentic assessment through digital technology to reduce documentation burdens, managing budgets transparently, and distributing workloads fairly alongside motivation-building measures. Subsequent guidelines emphasized individualized professional development through mentoring and building external networks to expand learning opportunities, particularly in small schools, with the ultimate goal of aligning institutional objectives with teachers’ own professional advancement.